2007
DOI: 10.1002/jcb.21516
|View full text |Cite
|
Sign up to set email alerts
|

Increased adipogenesis of osteoporotic human‐mesenchymal stem cells (MSCs) characterizes by impaired leptin action

Abstract: The bone marrow contains mesenchymal stem cells (MSCs) that differentiate to the osteogenic and adipogenic lineages. The fact that the decrease in bone volume of age-related osteoporosis is accompanied by an increase in marrow adipose tissue implies the importance that the adipogenic process may have in bone loss. We previously observed that MSCs from control and osteoporotic women showed differences in their capacity to differentiate into the osteogenic and adipogenic pathways. In vitro studies indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 59 publications
0
86
0
3
Order By: Relevance
“…Thus, statins may not be an osteogenic activator but rather an adipogenesis depressor, which may be attributed to their HMG-CoA inhibitory effect. Furthermore, recombinant leptin [34,35] , prostaglandins [36] and parathyroid hormone (PTH) [37] have recently shown significant osteogenic effects on MSCs. However, these hormones may lead to systemic side effects and are expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, statins may not be an osteogenic activator but rather an adipogenesis depressor, which may be attributed to their HMG-CoA inhibitory effect. Furthermore, recombinant leptin [34,35] , prostaglandins [36] and parathyroid hormone (PTH) [37] have recently shown significant osteogenic effects on MSCs. However, these hormones may lead to systemic side effects and are expensive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the action of leptin on the bone appears to have both positive and negative consequences and is not fully understood. Several in vitro studies have confirmed the positive effects of leptin on osteoblast proliferation, differentiation, and suppression of osteoblast-dependent osteoclast recruitment, while negatively regulating adipogenesis via their receptors expressed on both lineages [109][110][111][112]. A number of studies in mice have indicated the negative influence of leptin on bone metabolism and function because of its ability to enhance the sympathetic output to bone from the hypothalamus [113].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…Se puede observar que la presencia de leptina durante dicha diferenciación, disminuye significativamente el contenido de PPARγ sólo en las c-MSCs (Figura 2A, C) 74 . Puesto que la expresión de mARN para PPARγ fue similar en ambos tipos de células, se podría conjeturar la participación de algún tipo de regulación postraduccional para dar cuenta del alto contenido de PPARγ de las o-MSCs.…”
Section: A R T í C U L O D Eunclassified
“…Parece interesante, que la leptina agregada durante la adipogéne-sis aumentó significativamente el nivel de p-PPARγ sólo en las c-MSCs, lo cual es consistente con el efecto inhibitorio de leptina sobre la adipogénesis. En contraste, la presencia de la adipoquina durante la diferenciación adipogénica no cambió el nivel de p-PPARγ en las o-MSCs (Figura 2B y D) 74 . Se puede suponer que incluso cambios muy pequeños en la disponibilidad de PPARγ activo/inactivo afectaría el potencial adipogénico de las célu-las, debido a que ambos, mARN para PPARγ y la proteína tienen vida media corta 76 .…”
Section: A R T í C U L O D Eunclassified
See 1 more Smart Citation